'More Than Just Devotion': The Conservative Turn Among Subcultural Muslim Youths in the Indonesian Underground Music Scene - Saefullah, Hikmawan (Muslim Politics Review, 2022)
Scholars of Indonesian politics and Islam use the phrase ‘conservative turn’ to explain the increasing religious influence in contemporary Indonesia’s social, political, and cultural life. Although their literature provides insightful explanations about this trend, scholars fail to include subcultural Muslim youths in their analyses. The term ‘subcultural youths’ in this context refers to a diffuse network of young people that share distinctive identities, ideas, and cultural practices associated with underground music subcultures (such as punk, hardcore, hip-hop, metal, and ska) as a way to deal with a sense of marginalisation and/or to oppose mainstream society. In Indonesia in the 1990s, these youths were mostly secular, pluralist, and politically progressive and leftist. Their community welcomed all people from any social background, and religion was considered a personal matter. The social, political, and economic conditions following the fall of the New Order regime (1966-1998) changed the nature of this community. Some of its participants shifted ideologically and organisationally to Islamic conservatism and right-wing Islamism, marked by their support of and involvement in various movements such as the Islamic underground movement and the hijrah movement. This paper attempts to fill a gap within the existing literature on the conservative turn of subcultural youths in Indonesia by introducing the most recent subcultural theory as an analytical framework that can be used to explain the ideological and organisational shift. Studying the conservative turn of subcultural Muslim youths from a perspective that emphasises critical political economy allows this paper to present new insights against conventional wisdom and purely culturalist readings of the conservative turn in Indonesia.